(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Culture is the essence of self, core of individual identity. The novel Bombay Time taken for analysis is a clear representation of the fragmented childhood of Thrity Umrigar a Parsi writer. The title of the book itself signifies anecdotes of the old time it refers to Bombay as Bombay and not Mumbai as it is referred now by the millennials. This paper deals with different cultures of people they meet in an apartment. It talks about how they were, their ideologies, their dreams, their pasts and everything.